2022
DOI: 10.3389/fmicb.2022.883597
|View full text |Cite
|
Sign up to set email alerts
|

The ORF8 Protein of SARS-CoV-2 Modulates the Spike Protein and Its Implications in Viral Transmission

Abstract: COVID-19 is currently global pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Accompanying the rapid spread of the error-prone RNA-based genome, several dominant SARS-CoV-2 variants have been genetically identified. The mutations in the spike protein, which are essential for receptor binding and fusion, have been intensively investigated for their contributions to viral transmission. Nevertheless, the importance of other viral proteins and their mutations in SARS-CoV-2 lifecycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 55 publications
2
25
0
Order By: Relevance
“…The Δ382 strain replicates faster in vitro [20], but there is no significant change in the transcriptome of lung organoids infected with Δ382 [21]. ORF8 inhibits production of a viral component [22]. Consistently, we found that ORF8 restricts Spike incorporation into viral particles (Fig 7B ), and in turn, the virions were less infectious (Fig 7C).…”
Section: Discussionsupporting
confidence: 73%
“…The Δ382 strain replicates faster in vitro [20], but there is no significant change in the transcriptome of lung organoids infected with Δ382 [21]. ORF8 inhibits production of a viral component [22]. Consistently, we found that ORF8 restricts Spike incorporation into viral particles (Fig 7B ), and in turn, the virions were less infectious (Fig 7C).…”
Section: Discussionsupporting
confidence: 73%
“…An expression plasmid pcDNA3.1-SARS-CoV-2-Spike contains the wildtype (Wuhan strain) SARS-CoV-2 spike protein with a C-terminal C9 tag (gift from Fang Li; Addgene#145032). D614G or D614G plus N501Y (D614G/N501Y) mutation at Spike gene were performed by polymerase chain reaction (PCR) cloning [36] . The expression plasmid carrying spike gene derived from Beta strain (Academia Sinica, Taiwan), Delta strain (Addgene#179905) or Omicron strain (Addgene#179907) were used [37] .…”
Section: Methodsmentioning
confidence: 99%
“…Spike pseudovirions were produced as previously reported [36] . Different volumes of pseudovirions were inoculated with 3,000 HEK293T/hACE2 cells per well in 96-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies revealed a myriad of functions facilitated by ORF8, with implications for transmission dynamics, host immunity and male fertility. However, whether or not these functions depend on the dimeric form of the protein is yet to be determined 2325 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed a myriad of functions facilitated by ORF8, with implications for transmission dynamics, host immunity and male fertility. However, whether or not these functions depend on the dimeric form of the protein is yet to be determined [23][24][25] . NSP1 is a non-structural protein that causes a reduction in translation of cellular transcripts, promotes degradation of host mRNAs and inhibits export of nuclear mRNA, inhibiting host IFN-I response 26 .…”
Section: Mutations In Immunomodulatory Viral Proteins and Their Predi...mentioning
confidence: 99%